PENGARUH PENDIDIKAN KESEHATAN TENTANG SADARI TERHADAP PENGETAHUAN DAN SIKAP REMA`JA PUTRI DALAM UPAYA DETEKSI DINI KANKER PAYUDARA DI SMA YASPEND PABA TAHUN 2017 - Dona Seniorita (Jurnal Riset Hesti Medan, 2017)
Breast cancer is a breast disorder that is most feared by women, because this disease cannot be cured if found at an advanced stage. An effective effort to find breast cancer early is one of them is BSE (Self Breast Examination). The lack of information and efforts to publicize breast cancer early detection has led to the discovery and treatment of cancer that has not been managed properly. One effort to provide information about BSE to young women is through health education.This type of research is quasi-experimental research. The design used was pretestt-posttest with control group design. The population of all high school female students YASPEND PABA Binjai, samples were taken 50 respondents using simple random sampling technique, divided into two, namely 25 as the control group and 25 as the treatment group. The statistical test used is the Mann Whitney test with α = 5%.From the data analysis, it was found that there was an effect of health education about BSE on knowledge (p = 0,000) and the attitude (p = 0,000) of respondents in the effort of early detection of breast cancer.It is recommended for the school to work with the Health Office through the Binjai City Education Office to organize counseling activities on BSE. so that teenagers can apply BSE routinely in daily life as an effort to detect breast cancer early.